The impact of climate change on tourism and socio-culture in Depok Beach - Na’umi Berliana; Tashia Merita; Robertus Saptoto; Apriasnita Siswani (Journal of Rural Tourism, 2024)
Purpose - This study aims to evaluate the impact of weather changes due to climate change on the environment and socio-culture of local communities at Depok Beach in Yogyakarta. It also seeks to identify mitigation strategies that could be applied to address these impacts.Methodology/Design/Approach - The study employs qualitative descriptive methods. Data were collected through interviews, observations, and literature reviews to assess the effects of weather changes on the beach and its community.Finding - The results of the study show that weather phenomena such as abrasion, extreme rainfall, and rising air temperatures are affecting both the tourist attraction and the ecosystem sustainability of Depok Beach. Additionally, the interaction between tourists and the local community poses challenges in maintaining cultural values. Originality/Value - The study emphasizes the need for a sustainable tourism approach that integrates adaptation to weather changes with the preservation of socio-cultural values. It highlights the importance of finding solutions that balance environmental sustainability with cultural conservation in the face of climate change.